PENGEMBANGAN E-MODUL BERBASIS MIND MAPPING PADA MATA PELAJARAN PRODUK KREATIF DAN KEWIRAUSAHAAN KELAS XI SEKOLAH MENENGAH KEJURUAN - Enna Nainggolan; Arif Rahman (Universitas Negeri Medan, 2023)
Abstract The problem in this study is the large number of unemployed in Indonesia as many as 8.4 million people until February 2022, the majority of whom come from Vocational High Schools (SMK). This development research aims to (1) Determine the feasibility of Mind Mapping-Based E-Modules on Creative Products and Entrepreneurship Subjects Class XI Middle School Vocational Schools, and (2) Knowing the effectiveness of Mind Mapping-Based E-Modules on Creative Products and Entrepreneurship Subjects for Class XI Vocational High Schools. This research was conducted at SMK N 14 Medan. The method used in this research is research and development. The research and development process is carried out in several stages adapted from the ADDIE development research model. The stages are: Analysis (Analysis), Design (Design), Development (Development), Implementation (Implementation), and Evaluation (Evaluation). The results of this study are: (1) The results of the media feasibility validation are 3.86 with the